APLIKASI HASIL PENELITIAN PENDAMPINGAN KADER DAN KELUARGA TERHADAP TINGKAT PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG KUNJUNGAN ANTENATAL SERTA TES HIV - Dina Indrati Dyah Sulistyowati (Jurnal Salingka Abdimas, 2022)
Abstract Background: Each year it is estimated that more than 800,000 babies become infected with HIV as a result of mother-to-child transmission. If there are no precautions, there will be 3000 babies who are feared to be born HIV positive every year in Indonesia. One of the government's efforts is a program to prevent HIV transmission from mother to child, namely with HIV testing mandatory to offer to all pregnant women. The purpose of this community service is to find out how the application of Social Support Care Motivator: Assistance of Cadres and Maternal Affection Families on the Level of Knowledge and Attitudes of Pregnant Women About Antenatal Visits and HIV Test Recommendations in Purwokerto region